THE EFFECT OF CRITICAL TRACTION IN COHESIVE ZONE MODEL FOR FATIGUE CRACK GROWTH RETARDATIO - Dahlan, Hendery (Universitas Muhammadiyah Surakarta, 2016)
A cohesive zone model for simulation of fatigue crack growth is presented. The cohesive zone model is one of many alternative approaches used to simulate fatigue crack growth. The model incorporates a relationship between cohesive traction and separation in the zone ahead of a crack tip. The model introduces irreversibility into the constitutive relationships by means of damage accumulation with cyclic loading. The traction-separation relationship underpinning the cohesive zone model is not required to follow a predetermined path, but is dependent on irreversibility introduced by decreasing a critical cohesive traction parameter. The approach can simulate fatigue crack growth without the need for re-meshing and caters for single overloading. This study shows the retardation phenomenon occurring in elastic plastic-materials due to single overloading. Increasing the value of critical cohesive traction increases the extent of plastic zone at the crack tip which causes the fatigue crack growth to retard. Plastic materials can generate a significant plastic zone at the crack which is shown to be well captured by the cohesive zone model approach.